REVITALISASI ISU-ISU STRATEGIS MANAJEMEN SUMBER DAYA MANUSIA SEBAGAI SALAH SATU UPAYA MEMINIMALISIR KORUPSI - Eris Yustiono (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
Corruption has became an epidemic that is very hard to be cured. It damages manyaspects of life and becomes the main factor in creating poverty. Each regime tries todestroyed this disease but none is successful. So, destroying corruption looks like amission impossible. Actually, it is not a cureless disease. Revitalizing some strategicissues on human resourse management is one approach that can be proposed tominimized corruption